Ultrasonography Diagnosis and Imaging-Based Management of Thyroid Nodules: Revised Korean Society of Thyroid Radiology Consensus Statement and Recommendations - Shin, Jung Hee; Baek, Jung Hwan; Chung, Jin; Ha, Eun Joo; Kim, Ji-hoon; Lee, Young Hen; Lim, Hyun Kyung; Moon, Won-Jin; Park, Jeong Seon; Choi, Yoon Jung; Hahn, Soo Yeon; Jeon, Se Jeong; et al. (Korean journal of radiology, 2016)
The rate of detection of thyroid nodules and carcinomas has increased with the widespread use of ultrasonography (US), which is the mainstay for the detection and risk stratification of thyroid nodules as well as for providing guidance for their biopsy and nonsurgical treatment. The Korean Society of Thyroid Radiology (KSThR) published their first recommendations for the US-based diagnosis and management of thyroid nodules in 2011. These recommendations have been used as the standard guidelines for the past several years in Korea. Lately, the application of US has been further emphasized for the personalized management of patients with thyroid nodules. The Task Force on Thyroid Nodules of the KSThR has revised the recommendations for the ultrasound diagnosis and imaging-based management of thyroid nodules. The review and recommendations in this report have been based on a comprehensive analysis of the current literature and the consensus of experts.